2013
DOI: 10.1002/smll.201202476
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Surface Chemistry on the Toxicity of Ag Nanoparticles

Abstract: The role of surface chemistry on the toxicity of Ag nanoparticles is investigated using Saccharomyces cerevisiae yeast as a platform for evaluation. Combining the shape-controlled synthesis of Ag nanoparticles with a comprehensive characterization of their physicochemical properties, an understanding is formed of the correlation between the physicochemical parameters of nanoparticles and the inhibition growth of yeast cells upon the introduction of nanoparticles into the cell culture system. Capping agents, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 40 publications
(46 reference statements)
1
39
0
Order By: Relevance
“…As yeast cell walls were rigid, it could be supposed that under typical conditions nanoparticles cannot enter the cell (23,43,60). TEM observation also confirmed that no particles were inside yeast cells when cells were cultivated with CuO-NPs in our study (data not shown).…”
Section: Figsupporting
confidence: 77%
See 2 more Smart Citations
“…As yeast cell walls were rigid, it could be supposed that under typical conditions nanoparticles cannot enter the cell (23,43,60). TEM observation also confirmed that no particles were inside yeast cells when cells were cultivated with CuO-NPs in our study (data not shown).…”
Section: Figsupporting
confidence: 77%
“…After being cultivated with CuO-NPs, copper salt, and bCuO in 5 ml of SD medium for 4 h, the yeast cells were harvested by centrifugation at 8,000 ϫ g for 10 min and washed with PBS (pH 7.2) two times to remove copper adsorbed to the surface of the yeast (41,42). The process of separating nanoparticles from cells followed a method described previously (43). Briefly, 2 ml of ferric nitrate (1 mol/liter) was added into the sample as etchant solution; after 5 min of etching, the solution was removed by centrifugation, and samples were washed two times again with PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was widely reported that AgNP-induced biological effects or toxicities were mainly involved with silver ion release or intracellular ROS generation, 7,11,39 although some studies emphasized that AgNPs could efficiently induce oxidative stress through excessive ROS production, which was distinct from silver ions. 17 The results obtained herein revealed the concurrence of Ag + and ROS in AgNP-exposed bacterial system, showing the complexity of the antibacterial effects induced by AgNPs.…”
mentioning
confidence: 57%
“…The biologically active radical species are capable of attacking the cell membrane, posing oxidative stress, or even causing death to the cells. [15][16][17] Meanwhile, the released silver ions can approach negatively charged cell membrane and interfere with its integrity. 1 Moreover, the internalized AgNPs through endocytosis or pinocytosis may pose a Trojan-horse-type effect, releasing silver ions in the cytoplasm through the reactions with organelles such as mitochondria.…”
Section: Long Et Almentioning
confidence: 99%